Naturhänsynen i FSC-standarden - Dahl, Lena (2005)
The Swedish FSC standard (Forest Stewardship Council) is a level standard used to certify forestry. All the major Swedish forest companies are using the FSC standard, and approximately 50% of the Swedish forests are FSC certified today. In the essay six items within the chapter on environmental issues and biodiversity are examined: the proportion of protected forest, the proportion of annually burnt clear-cut stands, the number of trees with large diameter, the amount of dead wood, the proportion of deciduous trees within a stand and the proportion of deciduous-dominated stands. The FSC standard states a level for all items, and the purpose of the essay is to analyse whether these levels are supported by research within the field of conservation biology. The validity of the levels of the six items is them discussed to evaluate whether changes are required to the next revision of the FSC standard. The conclusions of the essay are based on historical data and research pursued in natural forests. The levels of the FSC standard are compared with the levels of the natural forest. In all Swedish vegetation zones the amount of dead wood is the most important item to increase for the next revision of the standard. In the boreal zone of Sweden the second most important item to increase is the proportion of burned clear-felled stands. In the boreonemoral and nemoral zones of Sweden the second most important item to increase is the proportion of deciduous-dominated stands. Although the FSC-standard is the first step towards environmentally appropriate forestry, there is still a long way to go before the biodiversity of the forests is secured and its role for fundamental processes and production capacity of the ecosystems is fully understood.